HUBUNGAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) DENGAN HIPERTENSI DI WILAYAH KERJA UPT PUSKESMAS DARUSSALAM KOTA MEDAN TAHUN 2024 - Gultom, Yohana Nursulyawati; Brahmana , Nettietalia Br; Nababan, Donal; Munthe, Seri Anawati (Akupun Tour Publisher, 2024)
Background: Prolanis is a program for managing chronic diseases such as hypertension and diabetes mellitus which is quite effective and efficient, but there are still many people who have not utilized this service. Hypertension is considered a serious health problem because it often occurs without complaints and can cause death (silent killer). Purpose: The aim of this research is to analyze the relationship between the chronic disease management program (Prolanis) and hypertension in the work area of ​​the UPT Puskesmas Darussalam Medan City in 2024. Method: This type of research is quantitative with a cross-sectional research design approach. The number of samples was determined using the Slovin formula as many as 93 people. Primary data collection was carried out directly through questionnaires and secondary data was obtained from the Darussalam Health Center, Medan City. Data analysis was carried out using univariate and bivariate methods. Univariate analysis was carried out to obtain a description of the research variables and bivariate analysis was carried out to test the hypothesis of the relationship between Prolanis and hypertension. Hypothesis testing uses the Chi-square statistical test. Based on statistical analysis, medical consultation was obtained (p=0.000), group education (p=0.000), SMS gateway reminder (p=0.000), home visit (p=0.001), health status monitoring (p=0.000). Disscusion and Conclusion: All variables studied are related to whether blood pressure is controlled or not, where these various variables, if implemented properly, will be beneficial for the stability of blood pressure. It is hoped that this research can provide recommendations for further improving chronic disease management programs to achieve a more optimal quality of life.